A comparison land-water environment of maximal voluntary isometric contraction during manual muscle testing through surface electromyography - Castillo-Lozano, Romualdo; Cuesta-Vargas, Antonio (BMC Springer Nature, 2013)
Background: The aim of this study was to compare through surface electromyographic (sEMG) recordings of the maximum voluntary contraction (MVC) on dry land and in water by manual muscle test (MMT). Method: Sixteen healthy right-handed subjects (8 males and 8 females) participated in measurement of muscle activation of the right shoulder. The selected muscles were the cervical erector spinae, trapezius, pectoralis, anterior deltoid, middle deltoid, infraspinatus and latissimus dorsi. The MVC test conditions were random with respect to the order on the land/in water. Results: For each muscle, the MVC test was performed and measured through sEMG to determine differences in muscle activation in both conditions. For all muscles except the latissimus dorsi, no significant differences were observed between land and water MVC scores (p = 0.063-0.679) and precision (%Diff = 7-10%) were observed between MVC conditions in the muscles trapezius, anterior deltoid and middle deltoid. Conclusions: If the procedure for data collection is optimal, under MMT conditions it appears that comparable MVC sEMG values were achieved on land and in water and the integrity of the EMG recordings were maintained during wáter immersion.
Keywords: Electromiografía; Surface electromyography; Aquatic exercise; Rehabilitation